Singapore: Reflecting on the development of the domestic mediation scene - CHUA, Eunice (Institutional Knowledge at Singapore Management University, 2015)
Amidst all the attention that Singapore has attracted as an international dispute resolution hubwith the recent launches of the Singapore International Mediation Centre (“SIMC”), SingaporeInternational Mediation Institute (“SIMI”) and the Singapore International Commercial Court,it is appropriate to pause to reflect on how far the domestic mediation scene has come in orderto support these global ambitions.